ANALISIS PENGENDALIAN KUALITAS PRODUK BERBASIS STATISTICAL QUALITY CONTROL (STUDI KASUS PADA PT APPAREL ONE INDONESIA) - Muhammad Naufal Luthfi; Rustono Rustono; Khairul Saleh (Politeknik Negeri Semarang, 2016)
This study aims to determine how is the implementation of quality control products conducted in PT Apparel One Indonesia by using statistical methods. The data collecting method in this study is direct observation conducted in August 2015. Analysis of quality control is done using statistical methods contained in Statistical Quality Control (SQC) such as check sheets, histograms, p-charts, pareto charts and cause-effect diagram. C Chart analysis results indicate that there are four days which are still experiencing irregularities. Data on the number 14 (August 21th) and 16 (August 25th) has passed the lower limit which means percentage failure is good enough to close to 0. However the data number 13 (August 20th) and 18 (August 27th) the failure has passed the upper limit where the failure is reach 7.60 % and 8.14 % indicates that the process is in a state of uncontrolled or still experiencing irregularities. Based on Pareto diagram, it can be seen that the failure is mostly caused by skip at 30.4% followed by puckering 20.4 % then cleanliness 18.4 %, caused by broken 17.5 % and measure 13.3 %. From the analysis of cause-effect diagram, it is also seen that the factors causing products failure is derived from human factors, machinery production, working methods, materials/ raw materials and work environment. In order to prevent failure, the company can take preventive and corrective measures to reduce the level of product failure and improve product quality, such as training the worker, doing maintenance regularly, and inspection on the material quality.